Studying the onset of galvanic steel corrosion in situ using thin films: film preparation, characterization and application to pitting. (8th January 2021) - Garai, Debi; Solokha, Vladyslav; Wilson, Axel; Carlomagno, Ilaria; Gupta, Ajay; Gupta, Mukul; Reddy, V Raghavendra; Meneghini, Carlo; Carla, Francesco; Morawe, Christian; Zegenhagen, Jörg
Abstract: This work reports about a novel approach for investigating surface processes during the early stages of galvanic corrosion of stainless steel in situ by employing ultra-thin films and synchrotron x-radiation. Characterized by x-ray techniques and voltammetry, such films, sputter deposited from austenitic steel, were found representing useful replicas of the target material. Typical for stainless steel, the surface consists of a passivation layer of Fe- and Cr-oxides, a couple of nm thick, that is depleted of Ni. Films of ≈4 nm thickness were studied in situ in an electrochemical cell under potential control (−0.6 to +0.8 V vs Ag/AgCl) during exposure to 0.1 M KCl. Material transport was recorded with better than 1/10 monolayer sensitivity by x-ray spectroscopy. Leaching of Fe was observed in the cathodic range and the therefor necessary reduction of Fe-oxide appears to be accelerated by atomic hydrogen. Except for minor leaching, reduction of Ni, while expected from Pourbaix diagram, was not observed until at a potential of about +0.8 V Cr-oxide was removed from the steel film. After couple of minutes exposure at +0.8 V, the current in the electrochemical cell revealed a rapid pitting event that was simultaneously monitored by x-ray spectroscopy. Continuous loss of Cr and Ni was observed during the induction time leading to the pitting, suggesting a causal connection with the event. Finally, a spectroscopic image of a pit was recorded ex situ with 50 nm lateral and 1 nm depth resolution by soft x-ray scanning absorption microscopy at the Fe L2, 3 -edges by using a 80 nm film on a SiN membrane, which is further demonstrating the usefulness of thin films for corrosion studies.